103k views
0 votes
HELP ME PLEASE!!!!!!

Find the remainder when f(x) is divided by (x - k).
f(x) = 4x3 - 6x2 + 3x + 1; k= -2

1 Answer

3 votes

Answer:

The remainder is -61

Explanation:

The polynomial remainder theorem states that the remainder of the division of a polynomial f(x) by (x-r) is equal to f(r).

The given polynomial is:


f(x) = 4x^3 - 6x^2 + 3x + 1

We need to find the remainder when f(x) is divided by x+2. According to the above-mentioned theorem, we only need to find f(-2) as follows:


f(-2) = 4(-2)^3 - 6(-2)^2 + 3(-2) + 1


f(-2) = 4(-8) - 6(4) - 6 + 1


f(-2) = -32 - 24 - 6 + 1=-61

The remainder is -61

User Pharaj Ali
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.